2009
DOI: 10.1016/j.juro.2009.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose Radiation Computerized Tomography Protocols on Distal Ureteral Calculus Detection

Abstract: Ultra low dose computerized tomography protocols detected distal ureteral calculi in a fashion similar to that of conventional computerized tomography protocols in a cadaveric model. These protocols may decrease the radiation dose up to 95%, reducing the risk of secondary malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 20 publications
0
33
0
1
Order By: Relevance
“…There have been studies on reduced-dose CT in cadavers in the United States and in small samples of selected populations outside the country. [12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…There have been studies on reduced-dose CT in cadavers in the United States and in small samples of selected populations outside the country. [12][13][14] These studies have also often excluded or found poor performance of nonsize-adjusted protocols in more obese patients, who are at increased risk for kidney stone and incur a higher radiation dose. 1,[15][16][17][18] Previous studies have also not followed patients receiving reduced-dose CT to determine its ability to predict outcomes and need for intervention.…”
Section: Background and Importancementioning
confidence: 99%
“…17 Although treatment modalities are different and include CT scan, they have though minimal, deleterious effects on the patients. 18,19 Most of the patients with UVJ and pre UVJ stones manifest LUTS. Patients manifesting LUTS do not require ureteric orifice dilatation and in them Ureteroscopy is relatively easy and time saving.…”
Section: Discussionmentioning
confidence: 99%
“…12,19,20 Ultrasonography is rarely used except in pregnancy and for children. 21 This study found that adverse events were rare when participating EPs felt a CT scan was not clinically indicated among adults ages 18 to 50 years with a first episode of suspected renal colic.…”
Section: Discussionmentioning
confidence: 99%
“…9 This is ill-advised as the accuracy of renal colic CT protocols in other diagnostic possibilities is unknown. 19,21,23 We attempted to measure this in our study by asking participating EPs at the start of our study if they were ordering the CT scan for other indications, and none said they did.…”
Section: Discussionmentioning
confidence: 99%